Effects of , a Multicomponent Breath-Based Yogic Practice (), on Perceived Stress and General Well-Being - Christine Tara Peterson PhD; Sarah M. Bauer BS; Deepak Chopra MD; Paul J. Mills PhD; Raj K. Maturi MD (SAGE Publishing, 2017)
Stress-induced disorders such as anxiety represent the leading causes of adult disability worldwide. Previous studies indicate that yoga and other contemplative practices such as pranayama , or controlled yogic breathing techniques, may be effective in the treatment of mood disorders and stress. In this study, 142 individuals (mean age = 43 years; SD = 13.90) participated in a 3-day retreat program during which they learned Shambhavi Mahamudra kriya , which is a yogic practice that includes both deep breathing and meditation techniques. Participants were instructed to practice the kriya each day for 21 minutes. After 6 weeks of daily practice, participants reported subjectively lower levels of perceived stress (Perceived Stress Scale) and higher levels of general well-being (General Well-Being Scale) compared to baseline. These results support the notion that Shambhavi Mahamudra kriya may represent a natural treatment for stress reduction.